Ayurvedic intervention in Bell’s palsy: case report on therapeutic efficacy - Lopez, Reeba; N., Navaneeth Krishnan; M. S., Aneesh (International Journal of Research in Medical Sciences, 2025)
Bell palsy is idiopathic, unilateral facial nerve palsy of acute onset leading to facial muscle weakness. Facial palsy is inflammation around the facial nerve and this pressure causes facial paralysis on the affected side. This is a case of A 46 year old male patient admitted in Kayachikitsa Department of Vaidyaratnam Ayurveda college, Ollur on 6th December 2023 with pain on the right side of face, posterior of neck radiating to right shoulder associated with swelling since one month. He had a history of Bell’s palsy before one month. Patient felt difficulty in speaking, closing of the right eyelid and loss of taste. He underwent a treatment protocol of Arditha followed by Vatavyadhi Chikitsa. Ayurvedic preparations like Dhanadanayanadi kashayam, Pathyashadankam kashayam, Vaiswanara choornam, Gandarvahastha eranda thailam, Dhanwantaram tablet were given internally. Choorna pinda swedam, Thalam with Rasnadi choornam and Karuthavattu, Rasathailam application, Sahacharadi tailam for whole body. Sirovasthi with Mahamasha tailam and Rasa tailam in the ratio 3:1 ratio, Ksheera dhoomam, Nasya with Anutailam were done externaly. House Brackmann Grade scales for pain, facial movements, were used to evaluate the effectiveness of treatment. Patient-reported outcome measures such as Facial Disability Index were used to assess the quality of life. Significant improvement noted in management of symptoms and work ability also showed improvement. Although this particular case was krichrasadhya, it was effectively managed through ayurvedic therapies, showing its relevance in current scenario that emphasises the invasive approaches.